Substance use and drug prevention among youth (The Journal of Psychology and Sociology, 2017)
The article considers the issues of drug abuse among young people and its prevention. In modern conditions for the state it is a very important task - to popularize among the youth of a healthy lifestyle, as well as the creation of all necessary conditions for the development of sports of high achievements, and for the active employment of the population in physical culture and sports. Prevention depending on narcotic drugs and psychotropic substances is a strategy aimed at reducing the risk factors of the disease or to enhance other factors which reduce susceptibility to disease. Certain circumstances in life may contribute to or impede the initiation of drug use. Life circumstances significantly increases the chances of an individual becoming a drug user were identified risk factors for drug use. Life circumstances, significantly reducing the chances of an individual becoming a drug user, called protection factors (protective factor) against the risk of drug use. Risk factors are often specific to a certain age and ethnic groups, to a certain social environment, and may depend on the type of drug used. Promotion of youth healthy lifestyles and prevention of alcoholic and drug dependence is an important task for the state and society. To identify how the Kazakh youth exposed to psychoactive substances, was carried out a pilot study. Preventive work is based on an integrated basis and is provided jointly by educators, teachers, psychologists, physicians, social workers, law enforcement personnel. Identification of individuals with drug problems and to date is very difficult. Virtually all medical and rehabilitation work in the area of Addiction As for explicit, advanced cases of drug addiction, substance abuse and alcoholism. The findings presented in this article.
Keywords: young people; healthy lifestyle; drugs; addiction; value; prevention; health.